Rapporter - Vandsø Andersen, Anette; Dvinge, Anne; Tessing Schneider, Magnus; Bale, John; Fjeldsøe, Michael; Holme Hansen, Thomas (Danish Yearbook of Musicology, 2007)
Research Projects Music and Enunciation (Anette Vandsø Andersen) Representations of Jazz in America at the Turn of the 21st Century (Anne Dvinge) Vocal Masks: The Rhetorical Singing Tradition in Italian Opera (Magnus Tessing Schneider) Conferences Sporting Sounds, University of Aarhus 2006 (John Bale) Shostakovich – today, Copenhagen October 2006 (Michael Fjeldsøe) Danish Musicological Society, 2006 (Thomas Holme Hansen)